Epidemiological studies on the HBV infection among the children at school age in S village in Gifu prefecture: Observation of anti-HBs positive for 6 years - MUTO, Yasutoshi; KAMETANI, Masaaki; TOKIMITSU, Naoki; GOI, Reiji; OKANO, Yasumasa; TSUDA, Fumio; TAKAKUWA, Kaoru; IWAI, Shoko; SUGIYAMA, Masato; TANAHASHI, Shinobu (Kanzo, 1984)
The HBV infection among the children at school age was investigated by the population study on HBV infection in S village in Gifu prefecture for 6 years. Of all examined in population survey in 1981, 23 HBsAg positive (1.9%) and 304 anti-HBs positive subjects (24.7%), including 6 HBsAg positive (2.4%) and 20 anti-HBs positive pupils (8.1%), were found. In S village there are K elementary schooi (66 pupils) and S elementary school (91 pupils). These schools have one class in the each grade. In K elementary school there was no HBsAg positive pupils and one anti-HBs positive pupil. In S elementary school 6 HBsAg positive and 14 anti-HBs positive pupils were found. In the latter school anti-HBs positive pupils were found only in the class with HBsAg positive pupils. Of 14 anti-HBs positive pupils, 11 pupils have converted from HBsAg positive during the study period. In these pupils, 10 pupils could not be infected within their families but at the school. Many of them, however, lived in the area where prevalence rate of HBsAg carrier was high so that the posibility of HBV infection at the school remained to be studied. During the observation period in S village a 10-yr-pupil was found to become HBsAg positive and healthy carrier except the cases of the maternal transmission.